An Analysis of Innovative Learning Media Development Needs Based on Realistic Mathematics Education - Ni Kadek Adhi Putri Pertiwi; I Made Wena; Kadek Adi Wibawa (Universitas Pendidikan Ganesha, 2023)
The difficulties of understanding in study mathematic is the learners use learning videos especially in pandemic situation. The purpose of this research is (1) to fine out the development of innovative learning videos based on realistic mathematics education in SMPN 4 Abiansemal. (2) to fine out the obstacles factors of innovative learning video development needs based on realistic mathematics education at SMPN 4 Abiansemal. (3) to fine out of the contributing factors of innovative learning video development needs based on realistic mathematics education at SMPN 4 Abiansemal. The method that used in this study is Descriptive method. The results of this study are (1) there are 2 teachers in the desperately needed category (100%), 18 learners in the desperately needed (60%), and 12 learners in the need category (40%). (2) the obstacles factor that teacher’s experiences is leak of video making skills and limited time they have. However, the problem that students face are limited Internet networking and the emergence of boredom. (3) supporting factors from teachers are the availability of tools to make and show videos and access of Internet. From the students, availability of tools to receive learning videos and sufficient Internet access. In conclusion, that teachers are desperate and some learners are desperate and some need with the development of the media mathematics base on realistic mathematics education. The obstacle factors: limited video making skill and time from the teacher, limited Internet networking, and boredom in the learners. Contributing factors: tools and the Internet are perfect suffice.